Pemanfaatan Google Bisnis dan Media Sosial untuk Optimalisasi Promosi dan Pencatatan Usaha Mikro - Ismael Ismael; Donny Sanjaya; Aulia Rahman Dalimunthe; Nugroho Syahputra; Cut Try Utari (Forum Kerjasama Pendidikan Tinggi, 2026)
Digital transformation has become a crucial strategy for enhancing the competitiveness and sustainability of Micro, Small, and Medium Enterprises (MSMEs), particularly in rural areas. Bengkel Las Siti Hajar, a micro-enterprise located in Sunggal District, Deli Serdang Regency, faces several challenges in business management, including conventional promotion methods, limited digital branding, and manual bookkeeping practices that reduce efficiency and accuracy. This Community Partnership Service Program (PKM) aims to strengthen the partner’s capacity to utilize simple digital technologies to support business promotion, financial record-keeping, and daily operations. The implementation methods included initial observations and interviews to identify the partner’s needs, training on the utilization of Google Business as a location-based promotional platform, assistance in creating promotional content through Instagram, and training on digital bookkeeping using Microsoft Excel-based applications. The results of the PKM implementation indicate a significant improvement in business performance, with an increase in monthly revenue of approximately 30%, a growth in regular customers from 8–10 to 15–20 individuals, and the development of a digital business portfolio that supports sustainable promotion. Furthermore, the partner demonstrated improved knowledge and skills in managing the business more professionally and systematically. Therefore, this community service activity confirms that the application of simple digital technologies can generate substantial positive impacts on the development, professionalism, and competitiveness of rural micro-enterprises.